2020
DOI: 10.1007/s00266-020-01916-7
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin Type A Injection for Mammoplasty and Abdominoplasty Scar Management: A Split-Scar Double-Blinded Randomized Controlled Study

Abstract: Background Scars are inevitable results of surgical procedures, and prevention of them is still a major problem in the field of cosmetic surgery. Although various studies have been performed on botulinum toxin-A (BoNT-A) injection for the prevention of hypertrophic scars, the exact mechanism remains unclear. Methods This prospective, double-blinded, randomized study was performed on 19 patients who underwent mammoplasty and abdominoplasty surgery in Razi Hospital from October 2018 to December 2019. Single sess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…All studies took post‐surgical wounds as intervention objects. Ten of them treated facial scars, 30–33,35–40 along with two studies treating thyroidectomy incisions, 41,42 one study treating median sternotomy wounds, 43 and one study treating mammoplasty and abdominoplasty wounds 44 . Seven studies were self‐control trials, 34,36,37,40,42–44 adopting whether split‐scar design or contralateral‐control design.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All studies took post‐surgical wounds as intervention objects. Ten of them treated facial scars, 30–33,35–40 along with two studies treating thyroidectomy incisions, 41,42 one study treating median sternotomy wounds, 43 and one study treating mammoplasty and abdominoplasty wounds 44 . Seven studies were self‐control trials, 34,36,37,40,42–44 adopting whether split‐scar design or contralateral‐control design.…”
Section: Resultsmentioning
confidence: 99%
“…Ten of them treated facial scars, 30–33,35–40 along with two studies treating thyroidectomy incisions, 41,42 one study treating median sternotomy wounds, 43 and one study treating mammoplasty and abdominoplasty wounds 44 . Seven studies were self‐control trials, 34,36,37,40,42–44 adopting whether split‐scar design or contralateral‐control design. Fourteen studies presented results of 6‐month follow‐up, 30,31,33–39,41–45 and three studies also reported results of longer follow‐up 32,34,40 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Scars are inevitable results of surgical procedures, and their prevention is still a major problem in the field of cosmetic surgery [ 50 ]. More importantly, the balance between the four primary steps of wound healing determines the dynamics of regeneration, and the outcome of wound healing, in particular, scar formation [ 51 ].…”
Section: Discussionmentioning
confidence: 99%